Strain Engineering of a MXene/CNT Hierarchical Porous Hollow Microsphere Electrocatalyst for a High‐Efficiency Lithium Polysulfide Conversion Process. Issue 5 (4th January 2021) - Wang, Xin; Luo, Dan; Wang, Jiayi; Sun, Zhenghao; Cui, Guoliang; Chen, Yuxuan; Wang, Tong; Zheng, Lirong; Zhao, Yan; Shui, Lingling; Zhou, Guofu; Kempa, Krzysztof; et al.
Abstract: Tensile‐strained Mxene/carbon nanotube (CNT) porous microspheres were developed as an electrocatalyst for the lithium polysulfide (LiPS) redox reaction. The internal stress on the surface results in lattice distortion with expanding Ti−Ti bonds, endowing the Mxene nanosheet with abundant active sites and regulating the d‐band center of Ti atoms upshifted closer to the Fermi level, leading to strengthened LiPS adsorbability and accelerated catalytic conversion. The macroporous framework offers uniformed sulfur distribution, potent sulfur immobilization, and large surface area. The composite interwoven by CNT tentacle enhances conductivity and prevents the restacking of Mxene sheets. This combination of tensile strain effect and hierarchical architecture design results in smooth and favorable trapping–diffusion–conversion of LiPS on the interface. The Li‐S battery exhibits an initial capacity of 1451 mAh g −1 at 0.2 C, rate capability up to 8 C, and prolonged cycle life. Abstract : Strain engineering of Mxene/carbon nanotube microspheres as electrocatalyst for Li‐S batteries is used to realize high‐efficiency LiPS catalytic conversion.